Cumulative impact assessments of multiple host species loss from plant diseases show disproportionate reductions in associated biodiversity. (18th November 2021) - Mitchell, Ruth J.; Bellamy, Paul E.; Broome, Alice; Ellis, Chris J.; Hewison, Richard L.; Iason, Glenn R.; Littlewood, Nick A.; Newey, Scott; Pozsgai, Gabor; Ray, Duncan; Stockan, Jenni A.; Stokes, Victoria; et al.
Abstract: Non‐native plant pests and pathogens are increasing exponentially, causing extirpation of foundation species. The impact of large‐scale declines in a single host on associated biodiversity is widely documented. However, the impact of multiple host loss on biodiversity and whether these impacts are multiplicative has not been assessed. Ecological theory suggests that systems with greater functional redundancy (alternative hosts) will be more resilient to the loss of sympatric hosts. We test this theory and show its importance in relation to pest/pathogen impact assessments. We assessed the potential impact on biodiversity of the loss of two widely occurring sympatric European tree species, Fraxinus excelsior and Quercus petraea/robur, both of which are currently threatened by a range of pests and pathogens. At the UK scale, the total number of associated species at risk of extirpation from plant diseases affecting these two sympatric hosts is greater than the sum of the associated species at risk from declines in either host alone. F. excelsior hosts 45 obligate species (species only found on that host) and Q. petraea/robur hosts 326. However, a decline in both these trees would impact 512 associated species, across multiple taxon groups, a 38% increase. Assessments at a local scale, 24 mixed F. excelsior–Q. petraea/robur woodlands revealed that these impacts may be even greater due to a lack of functional redundancy. Only 21% of sites were able to provide functional redundancy for F. excelsior and Q. petraea/robur associated species which can use other tree species. In most woodlands, the tree species required to provide functional redundancy were not present, although the site conditions were often suitable for them to grow. Synthesis . Understanding of functional redundancy should be applied to assessments of pests/pathogens impact on biodiversity. In risk assessments, higher impact scores should be given to pests/pathogens affecting hosts occurring with other host plant species already impacted by pests/pathogens. Current pest/pathogen risk assessment approaches that ignore the cumulative, cascading effects shown in this study may allow an insidious, mostly overlooked, driver of biodiversity loss to continue. Abstract : Understanding of functional redundancy should be applied to assessments of pests/pathogens impact on biodiversity. In risk assessments, higher impact scores should be given to pests/pathogens affecting hosts occurring with other host plant species already impacted by pests/pathogens. Current pest/pathogen risk assessment approaches that ignore the cumulative, cascading effects shown in this study may allow an insidious, mostly overlooked, driver of biodiversity loss to continue.